Escrita acadêmica e identidade: o processo de apropriação de gêneros acadêmicos por graduandos indígenas - Gomes, Glaucia Regina (2014)
Due to the challenges faced by the indigenous graduates when entering the university, taking the academic writing in general into consideration, this study aims to investigate how the process of appropriation of academic genres affect these groups in relation to their identity. The identification, the comprehension and the analysis of this context were held from the theoretical conceptions of the New Literacy Studies (STREET, 1984; GEE, 2004; LEA & STREET, 1998; KLEIMAN, 2007, among others), as well from assumptions that aim at the teaching, the analysis of academic genres (MATENCIO, 2002; MACHADO, LOUSADA E ABREU-TARDELLI, 2004A; 2004B, among others), and also the identity conceptions (GIDDENS, 1991, 2002). From this perspective, it is considered that the Academic Literacy differs from literacy of other spheres, because it presents particular forms of being, thinking, acting, reading and writing that are fit at this sphere, so the College student, in order to acquire fluency in Academic Discourse, must master them. On the assumption, that the genres of discourse mediate social practices and they participate of the Constitution of social relations, of values, of identities (MEURER 2005), we understand that the domain of written texts of different genres promotes the development of the ability of language use by the subject and they constitute the subject himself as such (SCHNEUWLY, 2004). Thereby, the academic genre is our focus that can be considered as complex genre, secondary (BAKHTIN, 2000). To develop such research, we used our studies along our graduate school at Federal University of São Carlos, among them: the activities in ACIEPES3 in the years of 2010 and 2011, individualized care and access to textual written productions of indigenous from various courses4, from the approval of the Ethics Committee, under the number of the certificate of introduction to Ethics Assessment (CAAE) 17948113.7.0000.5504. This study is characterized as a qualitative research ethnographically, from which we choose the paradigm or epistemological model indicting (GINZBURG, 1990), that allows you to establish relationships among the literacy stories of the subjects of research, literate practices, practices of academic sphere and the conflicts that emerge from these practices.